Astrocytes and microglia but not neurons preferentially generate N-terminally truncated A? peptides - Oberstein, Timo; Spitzer, Philipp; Klafki, Hans-Wolfgang; Linning, Philipp; Neff, Florian; Knoelker, Hans-Joachim; Lewczuk, Piotr; Wiltfang, Jens; Kornhuber, Johannes; Maler, Juan Manuel (Neurobiology of Disease, 2015)
The neuropathological hallmarks of Alzheimer's disease include extracellular neuritic plaques and neurofibrillary tangles. The neuritic plaques contain ?-amyloid peptides (A? peptides) as the major proteinaceous constituent and are surrounded by activated microglia and astrocytes as well as dystrophic neurites. N-terminally truncated forms of A? peptides are highly prevalent in neuritic plaques, including A? 3-x beginning at Glu eventually modified to pyroglutamate (A? N3pE-x), A? 2-x, A? 4-x, and A? 5-x. The precise origin of the different N-terminally modified A? peptides currently remains unknown. To assess the contribution of specific cell types to the formation of different N-terminally truncated A? peptides, supernatants from serum-free primary cell cultures of chicken neurons, astrocytes, and microglia, as well as human astrocytes, were analyzed by A?-ELISA and one- and two-dimensional SDS-urea polyacrylamide gel electrophoresis followed by immunoblot analysis. To evaluate the contribution of ?- and ?-secretase to the generation of N-terminally modified A?, cultured astrocytes were treated with membrane-anchored "tripartite ?-secretase (BACE1) inhibitors" and the ?-secretase inhibitor DAPT. Neurons, astrocytes, and microglia each exhibited cell type-specific patterns of secreted A? peptides. Neurons predominantly secreted A? peptides that begin at Asp1, whereas those released from astrocytes and microglia included high proportions of N-terminally modified A? peptides, presumably including A? 2/3-x and 4/5-x. The inhibition of BACE1 reduced the amount of A? 1-x in cell culture supernatants but not the amount of A? 2-x.
EVALuna2:23718